Learning About CEO Ability and Stock Return Volatility - Pan, Yihui; Wang, Tracy Yue; Weisbach, Michael S. (Review of Financial Studies, 2015)
Consistent with predictions from a stylized Bayesian learning model stock return volatility declines with CEO tenure in a convex manner, even for CEOs whose appointments occur for exogenous reasons. The decline is faster when there is higher uncertainty about the CEO's ability when there is more transparency about the firm's prospects, and when CEO ability is more important in value creation. We quantify the importance of uncertainty about CEO ability relative to the firm's fundamental cash flow uncertainty in contributing to stock return volatility, highlighting the importance of management in creating value.